Pengaruh Citra Merek, Customer Experience, Dan Word Of Mouth Terhadap Minat Beli Ulang Starbucks Coffee Di Blimbing Kota Malang - Rika Indriyati; Rois Arifin; Satria Putra Utama (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This research was conducted with the aim to determine the effect of brand image on repurchase intention, to determine the effect of customer experience on repurchase intention, to determine the effect of word of mouth on repurchase intention. The population used in this study is Starbuck Coffee in Blimbing, Malang city. By using the purposive sampling method as a sampling technique. This study uses multiple linear regression analysis, by testing the hypothesis using the t test. The results of this study indicate that brand image has a significant effect on repurchase intention, customer experience has a significant effect on repurchase intention, Word of Mouth has a significant effect on repurchase intention. Keywords: Brand Image, Customer Experience, Word Of Mouth, Repurchase Intention